Accounting made simple - Hingley, Wilfred (Oxford, England : Made Simple Books, 1989)
Introduces the reader to all the major aspects of financial and management accounting. It provides a basis of study for the foundation and intermediate stages of the professional accountancy organizations. The emphasis is on statements, procedures and interpretation.
Includes index.
kjo 15/01/2019
Loans
Keywords: Accounting